THE EFFECT OF CORPORATE GOVERNANCE ON R&D INVESTMENT WITH FINANCIAL SLACK AS A MEDIATING VARIABLE - Riantoni, Ivan Akbar (I-Finance Journal, 2023)
The aim of this research is to examine the influence of corporate governance structures, namely independent commissioners and institutional ownership, on research and development (R&D) investment mediated by financial slack in pharmaceutical companies listed on the Indonesian Sharia Stock Index (ISSI) on the Indonesia Stock Exchange during the period (2018-2022). Data were extracted from annual reports and financial statements, with a total of 7 pharmaceutical companies listed on the ISSI serving as the sample. The analytical technique employed was the multiple regression test using panel data, conducted using Eviews. The research findings indicate that financial slack has a positive and significant effect on R&D investment. Independent commissioners have no significant effect on R&D investment. Institutional ownership has a significant effect on R&D investment. Then independent commissioners affect R&D investment through financial slack as a mediating variable, and institutional ownership has no effect on R&D investment through financial slack as a mediating variable. The conclusion is that the greater the level of financial slack, the higher the allocation of funds in R&D investment. Therefore, it is important to choose independent commissioners who are competent according to the company’s sector. On the other hand, institusional ownership is able to increase control over management because it has intensive knowledge, experience, and more networks.